Parallelization of Microfluidic Droplet Junctions for Ultraviscous Fluids (Small 48/2022). Issue 48 (1st December 2022) - Kim, Hyeon Ho; Cho, YongDeok; Baek, Dongjae; Rho, Kyung Hun; Park, Sung Hun; Lee, Seungwoo
Abstract : Ultraviscous Fluids In article number 2205001 by Seungwoo Lee and co‐workers, a 2D branched droplet microfluidic device for ultraviscous fluid is designed and fabricated. Parallelly arranged 64 T‐junctions compose the droplet microfluidic device. Each junction is specifically designed based on hydraulic resistance. Through the device, the fluid with a viscosity of 3.5 Pa.s (i.e., polydimethylsiloxane prepolymer) can be fabricated as monodispersed droplets. The production rate is ≈330 000 droplets per hour and the generated droplets have a 2∼3% coefficient of variation.